Indian Floriculture Industry : A Country-Wise Export Analysis - Kumar, Naresh (Arthshastra Indian Journal of Economics & Research, 2023)
Purpose : This paper aimed to improve understanding of India’s floricultural exports. It attempted to examine India’s floricultural export performance in relation to the major importers of floriculture. Methodology : The data were analyzed using statistical approaches such as average, standard deviation (SD), coefficient of variation (CV), and CAGR. Six other indices were also considered. The analysis was entirely dependent on secondary data. Findings : India’s floriculture production met domestic and international demand. In 2001â€“2002, India exported 18803.67 metric tons of floricultural goods for a total of â‚¹Â 115.30 crores. In 2021â€“2022, the export was 23597.17 metric tons worth â‚¹Â 771.41 crores. From 2009â€“2010 to 2021â€“2022, the CAGR was 2.779% of total floriculture exports. Malaysia, Hungary, Singapore, and the United Arab Emirates are the top four leading importers of Indian floriculture goods, with CAGRs of 25.31%, 22.92%, 17.85%, and 12.69%, respectively. Practical Implications : The research paper advised that more incentives be given to stimulate floriculture exports. Some countriesâ€™ growth rates for India’s floriculture exports were low. As a result, increased demand for Indian floriculture from importing countries was critical. Based on the results of the country-by-country analysis, the export concentration was in a small number of countries, which caused worries for the Indian floriculture business. Originality : The current paper revealed an overall picture of Indian floriculture exports to facilitate the exporters.